Changes in the concentration and relative abundance of alkanes and PAHs from the Deepwater Horizon oiling of coastal marshes - Turner, R.E.; Overton, E.B.; Meyer, B.M.; Miles, M.S.; Hooper-Bui, L. (Marine pollution bulletin, 2014)
•We measured oil constituents in wetlands before and after the 2010 Macondo oil spill.•Twenty-two of 28 alkane analytes declined (0.40%day−1) and six did not.•Five PAHs increased (@ 0.24–0.70%day−1) over the first 2.5 years.•The application of 9 potential degradation/weathering indicators was unsuccessful. We determined changes of 28 alkanes and 43 different PAHs in 418 wetland soil samples collected on ten sampling trips to three Louisiana estuaries before and after they were oiled from the 2010 Deepwater Horizon disaster. There was a significant decline in 22 of the 28 alkane analytes (0.42%day−1), no change in 6, over 2.5years. The concentration of five aromatic petroleum hydrocarbons (PAHs) increased (range 0.25–0.70%day−1), whereas the total PAH pool did not change. Of these five, naphthalene and C-1-naphthalenes are suggested to be of higher toxicity than the other three because of their relatively higher volatility or solubility. The relative proportions of alkane analytes, but not PAHs, does not yet resemble that in the pre-oiled marshes after 3years, The trajectories of nine indicators for degradation/weathering were either inconclusive or misleading (alkanes) or confirmed the relatively meager degradation of PAHs.